Thermal heat-power stations on the basis of gas installations and steam turbines with low temperature operation body - Chepurnyi, M. M.; Tkachenko, S. Y. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Basis indices of thermal power stations of binary type with low temperature working body in the second cycle are determined.